The Chef and the Supplier: The Role of the Supply Chain in Fine Dining Creativity - Fusté Forné, Francesc; Leer, Jonatan (The International Journal of Sociology of Agriculture and Food, 2025)
This article studies the relationship between culinary creativity in fine dining restaurants and the supply chain that supports them. Fine dining has experienced a renaissance in recent decades, with chefs pushing the boundaries of culinary innovation. However, little attention has been given to the pivotal role that suppliers play in this creative process. Based on the exploration of four case studies of Michelin-starred restaurants in Denmark, the paper uncovers the ways in which the supply chain influences the dynamics of high-end restaurants, proposing a social-material perspective on culinary creativity. Results show how sourcing practices impact fine dining creativity, and highlight the role of nature and quality as the foundations of the relationships between chefs and suppliers. This research innovatively sheds light on the behind-the-scenes processes that drive fine dining and shows how different restaurants think differently about the role of suppliers in the creative process. The strategies involve more traditional chef-centred approaches to culinary creativity, as well as ambitions to become self-sufficient. Results also show that the restaurants put the farmers first, seeing the supply chain and the food system as central to culinary creativity. We argue that these approaches seem to be essential to the development of more sustainable forms of Michelin restaurants.